On the effects of 2D MXene on perovskite solar cells - Ng, Ryan Yi Ren (Nanyang Technological University, 2023)
Perovskite solar cells has seen many improvements and optimisation over the years since it was first synthesised in 2012. One commonly employed method to improve the efficiency of perovskite solar cells is additive engineering. A material that has also came under the spotlight recently is MXene. It has similar properties and structure to graphene, but better conductivity. It was also reported that MXene was able to increase the grain size of perovskite crystals as an additive in ETL and perovskite layer. In this report, we investigate how MXene affects the crystallisation mechanism when it is used as a substrate for perovskite crystals to grow on.